Multiple-level validation identifiesPARK2in the development of lung cancer and chronic obstructive pulmonary disease - SeungBaek Lee; Jun She; Bo Deng; Jung-Jin Kim; Mariza de Andrade; Jie Na; Zhifu Sun; Jason A. Wampfler; Julie M. Cunningham; Yanhong Wu; Andrew H. Limper; Marie-Christine Aubry; et al. (2016)
An important precursor to lung cancer development is chronic obstructive pulmonary disease (COPD), independent of exposure to tobacco smoke. Both diseases are associated with increased host susceptibility, inflammation, and genomic instability. However, validation of the candidate genes and functional confirmation to test shared genetic contribution and cellular mechanisms to the development of lung cancer in patients with COPD remains underexplored. Here, we show that loss of PARK2 (encoding Parkin) increases the expression of proinflammation factors as well as nuclear NF-κB localization, suggesting a role of PARK2 loss in inflammation. Additional exploration showed that PARK2 deficiency promotes genomic instability and cell transformation. This role of PARK2 in inflammation and chromosome instability provides a potential link among Parkin, COPD and lung cancer. A further comprehensive validation of 114 informative single nucleotide polymorphism (SNP) variants of PARK2, in 2,484 cases and controls with well-defined lung cancer and COPD phenotypes, found rs577876, rs6455728 and rs9346917 (p<0.01) to be significantly associated with lung cancer development in people with COPD. Our findings support the evidence that PARK2 might have a tumor suppressor role in the development of COPD and lung cancer.